2012
DOI: 10.1017/s0954579412000193
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of self-efficacy and depressive symptoms in youth of a North American Plains tribe

Abstract: We used a 3-year cross-sequential longitudinal design to examine the relations between self-efficacy judgments in three different domains (academic, social, resisting negative peer influences), cultural identity, theories of intelligence, and depressive symptoms. One hundred ninety-eight American Indian youths participated in the study, who all attended a middle school on a reservation in the northern plains of the United States. We conducted multilevel models to examine both between- and within-person associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 94 publications
2
19
1
Order By: Relevance
“…For instance, those who reported a medium score (4) for learning motivation, learning strategies, and management of learning resources at time two also tended to report lower scores for depression (−4.386, 95% CI: −7.596 to −2.076; −7.864, 95% CI: −11.408 to −4.32; −4.628, 95% CI: −6.876 to −2.38, respectively). Our findings were consistent with those of previous studies (Akin, 2008;Bandura, 2001;Ghaderi & Salehi, 2011;Scott & Dearing, 2012;Sideridis, 2005). However, those studies mainly focused on the effects of self-efficacy and goal orientation on depression, Table 3.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, those who reported a medium score (4) for learning motivation, learning strategies, and management of learning resources at time two also tended to report lower scores for depression (−4.386, 95% CI: −7.596 to −2.076; −7.864, 95% CI: −11.408 to −4.32; −4.628, 95% CI: −6.876 to −2.38, respectively). Our findings were consistent with those of previous studies (Akin, 2008;Bandura, 2001;Ghaderi & Salehi, 2011;Scott & Dearing, 2012;Sideridis, 2005). However, those studies mainly focused on the effects of self-efficacy and goal orientation on depression, Table 3.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, longitudinal research with North American Indian youth found that self-efficacy beliefs were related to lower depressive symptoms over time, and cultural identity did not moderate self-efficacy [69].…”
Section: Discussionmentioning
confidence: 96%
“…Estimates show that mood and/or anxiety disorders co-occur in up to half of people who have sought treatment for substance abuse problems (Langås et al 2011; Urbanoski et al 2015). Two constructs, specifically, hope and abstinence self - efficacy, are both related to goal pursuit and, thus, may have important affective consequences (Arnau et al 2007; Scott and Dearing 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In general, self-efficacy is an important predictor of depression and well-being (Chang et al 2011). In this context, individuals may experience depression when they doubt their ability to perform actions that are necessary for valued outcomes (Ahrens 1987; Scott and Dearing 2012). Although hope and self-efficacy are related constructs (Ferrari et al 2012), research has supported a theoretical and empirical distinction between the two (Hartley et al 2008; Magaletta and Oliver 1999).…”
Section: Introductionmentioning
confidence: 99%